In vitro effects of different levels of quebracho and chestnut tannins on rumen methane production, fermentation parameters, and microbiota - Battelli, Marco; Colombini, Stefania; Parma, Pietro; Galassi, Gianluca; Crovetto, Gianni Matteo; Spanghero, Mauro; Pravettoni, Davide; Zanzani, Sergio Aurelio; Manfredi, Maria Teresa; Rapetti, Luca (Frontiers in Veterinary Science, 2023)
Both condensed and hydrolysable tannins (CTs and HTs, respectively) have the ability to reduce enteric CH4 production in ruminants. However, the precise mechanism of action is not fully understood. Among the proposed hypotheses are the reduction of ruminal digestibility, direct control action on protozoa, reduction of archaea, and a hydrogen sink mechanism. In this in vitro study, which simulated rumen fermentation, two additives, one containing CTs (70% based on DM) from quebracho and one with HTs (75% based on DM) from chestnut, at four levels of inclusion (2, 4, 6, 8% on an as-fed basis) were added to the fermentation substrate and tested against a negative control. Both types of tannins significantly reduced total gas (GP) and CH4 (mL/g DM) production during the 48 h of incubation. The lower GP and CH4 production levels were linked to the reduction in dry matter digestibility caused by CTs and HTs. Conversely, no significant differences were observed for the protozoan and archaeal populations, suggesting a low direct effect of tannins on these rumen microorganisms in vitro. However, both types of tannins had negative correlations for the families Bacteroidales_BS11 and F082 and positive correlations for the genera Prevotella and Succinivibrio. Regarding the fermentation parameters, no differences were observed for pH and total volatile fatty acid production, while both CTs and HTs linearly reduced the NH3 content. CTs from quebracho were more effective in reducing CH4 production than HTs from chestnut. However, for both types of tannins, the reduction in CH4 production was always associated with a lower digestibility without any changes in archaea or protozoa. Due to the high variability of tannins, further studies investigating the chemical structure of the compounds and their mechanisms of action are needed to understand the different results reported in the literature.